QUALITY COST ANALYSIS FOR THE IMPROVEMENT OF DENIM FABRIC QUALITY - Annisa Novianti; Eka Wirajuang Daurrohmah (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2023)
Business competition in the economic industry encompasses both price and quality competition. Competitive advantage can be achieved when a company produces quality products at an appropriate price. This study aims to determine the extent to which PT X has implemented quality control to win the competition in the economic industry through the application of quality costs. The research method used in this study is descriptive research with a quantitative approach. Based on the research results, appraisal costs have the largest proportion, accounting for 87.58%, prevention costs are in second place with a percentage of 11.93%, and internal failure costs are the lowest with a percentage of 0.49%. The total quality costs generated meet the maximum standards, both according to the rule of thumb of 2.4% and the maximum company standard of 1% per division, which is 0.593%. This indicates that the quality control of PT X is well established, but the company needs to increase prevention costs, especially for training and education expenses, as well as machine calibration costs, in order to produce quality fabric and reduce defective products to a level of 0. This way, the company can achieve production efficiency.